2011
DOI: 10.1364/oe.19.011680
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Photo-induced defects in Ge-doped fiber/preform: influence of the drawing

Abstract: Abstract:We have studied the generation mechanisms of two different radiation-induced point defects, the Ge(1) and Ge(2) centers, in a germanosilicate fiber and in its original preform. The samples have been investigated before and after X-ray irradiation using the confocal microscopy luminescence and the electron paramagnetic resonance techniques. Our experimental results show the higher radiation sensitivity of the fiber as compared to the perform and suggest a relation between Ge(1) and Ge(2) generation. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…As shown in this figure, the UV irradiation generates NBOHCs, whose concentration increases, and reduces the GLPCs reservoir concentration. Similar results have been already obtained on X-irradiated Gedoped fibers [15] involving possible photo-induced processes for the conversion mechanisms of the Ge-related defects. Fig.…”
Section: Laser Effects During the Grating Inscriptionsupporting
confidence: 88%
“…As shown in this figure, the UV irradiation generates NBOHCs, whose concentration increases, and reduces the GLPCs reservoir concentration. Similar results have been already obtained on X-irradiated Gedoped fibers [15] involving possible photo-induced processes for the conversion mechanisms of the Ge-related defects. Fig.…”
Section: Laser Effects During the Grating Inscriptionsupporting
confidence: 88%
“…Notwithstanding insights (A) and (B) above, observed variations in the Ge(1)-to-Ge(2) concentration ratios at room temperature continue to convince some researchers that Ge(1) and Ge(2) cannot be two energetically different states of the same precursor (e.g., [21]). For example, in Figure 2 the Ge(1) : Ge(2) ratio is seen to be ∼2 : 1 after xirradiation at 100 K and a 5-min warming at 300 K [6], whereas this ratio has been found in [21] to be 0.8 : 1 for GeO 2 -doped silica optical fibers and preforms -irradiated at room temperature and stored at ambient temperatures for a full month before recording the data.…”
mentioning
confidence: 92%
“…For example, in Figure 2 the Ge(1) : Ge(2) ratio is seen to be ∼2 : 1 after xirradiation at 100 K and a 5-min warming at 300 K [6], whereas this ratio has been found in [21] to be 0.8 : 1 for GeO 2 -doped silica optical fibers and preforms -irradiated at room temperature and stored at ambient temperatures for a full month before recording the data. However, this is hardly a serious contradiction, given that in Figure 2 it is seen that a further 5-min anneal at 370 K also results in a Ge(1) : Ge(2) ratio of ∼0.8 : 1.…”
mentioning
confidence: 97%
“…Since the is shown to depend linearly on the , the increased is thought to be closely related to the concentration of the radiation-induced defects in the optical fiber. Note that previous spectroscopic studies in Ge-doped silica glasses through electron paramagnetic resonance (EPR), luminescence, and absorption measurements revealed that Ge-related defects are more efficiently formed than the Si-related defects, thus the most radiation-induced optical properties in the glasses have been mainly accounted for the Ge-related defects [7], [26]- [28]. On the basis of this, the change in of the gamma-ray irradiated fiber is thought to be mainly due to the Ge-related defects formed in the core of the fiber such as GeE', Ge(1), Ge(2), Ge related ODCs, self-trapped hole (STH), and nonbridging oxygen (NBO) hole defects.…”
Section: Resultsmentioning
confidence: 99%